2009
DOI: 10.19030/tlc.v6i5.1141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Achievement Goals, Meta-Cognition And Academic Success In Pakistan

Abstract: The research was the replication of the study done by Coutinho (2006) and it aimed at finding the relationship between achievement goals, meta-cognition and academic success. Achievement goals were further divided into two types: mastery and performance. The participants were 119 students enrolled in M. A. Education, Department of Education at the University of Sargodha. The questionnaire used in the original study, along with Urdu translation, was administered to the participants. The questionnaire consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
1
9
1
1
Order By: Relevance
“…This research endorses that male and female teachers had no difference in their opinion regarding the Programmed Learning and Metacognition of students at secondary schools in Karachi, Pakistan. This research confirms the research findings of Aleven, & Koedinger (2002), Sarwar et al, (2009) andBogdanovic et al (2015) who reported that metacognitive achievement highly depended upon the effective instructional model and not dependent on the gender of individuals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This research endorses that male and female teachers had no difference in their opinion regarding the Programmed Learning and Metacognition of students at secondary schools in Karachi, Pakistan. This research confirms the research findings of Aleven, & Koedinger (2002), Sarwar et al, (2009) andBogdanovic et al (2015) who reported that metacognitive achievement highly depended upon the effective instructional model and not dependent on the gender of individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Hennessey (1999) added that students had acquired and exhibited positive qualitative changes in their Metacognition skills when effective Programmed Learning exposure offered from the teachers. Contrary, Sarwar et al (2009) found no significant relationship between Metacognition and academic achievements of students in the context of Pakistan.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…12,16 This is also in contradiction with the findings of Imran M et al, Rani R et al, Siddique A et al, and Ul Rehaman F et al who say that gender has no role to play in awareness of metacognition. 13,[17][18][19] One of the plausible reasons for males having better metacognitive awareness than females could be that the areas of the brain related to metacognition is better developed in males, this area being the prefrontal cortex. 20 Our research, also in sync with the above studies, shows better metacognitive awareness scores in males though it is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in their study which aimed to identify the relationship between success objectives, academic success and metacognition, Sarwar, Yousuf, Hussain and Noreen (2009) found no significant differences between metacognitive skills levels and the gender variable. The reason for the insignificant difference between total and planning dimensions in terms of gender could be the similar social conditions and limited social activities of the city the education faculty students live in.…”
Section: Discussion Conclusion and Implementationmentioning
confidence: 94%